Electric Load Modeling for Managing Electric Energy Consumption Through the PDCA Cycle in the Library Building of Andalas University - Refki Budiman; Refdinal Nazir (Andalas Journal of Electrical and Electronic Engineering Technology, 2023)
The need for electrical energy in the public building sector is quite dominant, reaching 33-40% of the total energy consumption of all sectors. To control electrical energy in buildings effectively, an Energy Management System (EMS) is needed. EMS stage consists of Plan-Do-Check-Act (PDCA). The study conducted in this research is on how to use the PDCA cycle method to model the consumption of electrical energy in campus buildings in a sustainable manner. Modeling of energy-efficient electrical loads is formed in several ways: modeling by replacing T8 fluorescent lamps and CFLs with LED, modeling by replacing non-inverter AC with inverter AC, modeling by the number of library visitors, modeling by improving the power factor, and finally, modeling with a combination of the four previous models. Modeling using LEDs results in savings of 1,464 kWh per month; inverter AC modeling saves 1742 kWh per month; modeling by adjusting the number of visitors saves 857 kWh per month; and modeling by improving the power factor saves 56 kWh per month. This electrical load modeling can save up to 8 kW of power outside of the library's operating hours. Meanwhile, during operational hours, the modeling library can save up to 30 kW of electric power